Information integration of cad tools for thermal design of microelectronic devises components at critical modes of functioning - Fedasyuk, D.; Bobalo, S.; Markelov, O. (Українські технології, 2006)
This paper presents the concepts of the Network-based information integration of CAD tools for the thermal design. The system architecture is built on power information technologies and provides remote access to the thermal modeling engine of icroelectronic devices and their components via Internet/Intranet.
Keywords: information integration; CAD; thermal simulator; microelectronic